Microglia contribute to the propagation of Aβ into unaffected brain tissue - d’Errico, Paolo; Ziegler-Waldkirch, Stephanie; Aires, Vanessa; Hoffmann, Philippe; Mezö, Charlotte; Erny, Daniel; Monasor, Laura Sebastian; Liebscher, Sabine; Ravi, Vidhya M.; Joseph, Kevin; Schnell, Oliver; Kierdorf, Katrin; et al. (Nature Neuroscience, 2022)
Microglia appear activated in the vicinity of amyloid beta (Aβ) plaques, but whether microglia contribute to Aβ propagation into unaffected brain regions remains unknown. Using transplantation of wild-type (WT) neurons, we show that Aβ enters WT grafts, and that this is accompanied by microglia infiltration. Manipulation of microglia function reduced Aβ deposition within grafts. Furthermore, in vivo imaging identified microglia as carriers of Aβ pathology in previously unaffected tissue. Our data thus argue for a hitherto unexplored mechanism of Aβ propagation.
CRIS-Team Scopus Importer:2023-09-13